Career Trajectories of Bachelor of Secondary Education Graduates: A Tracer Study for Strategic Educational Enhancements: Tracer Study, Graduate Employability, Employment Status, Teacher Education - Salendab, Fahad A.; Dapitan, Yolanda C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study investigates the employability and career trajectories of Bachelor of Secondary Education (BSED) graduates of Sultan Kudarat State University (SKSU)—Kalamansig Campus from 2018 to 2022. It employs a descriptive research design to gather data.The respondents were 137 BSED graduates selected using conven-ience sampling. The study utilized the Commission on Higher Educa-tion (CHED) standardized questionnaire but modified it to align with its objectives. This questionnaire was distributed via an online sur-vey platform. Statistical treatment involved frequency and percent-age.Results revealed that most graduates were in the 26-30 age group, with females outnumbering males and most residing in municipality areas. Graduates cited career advancement and attractive compensa-tion as key reasons for taking the BSED program, supported by insti-tutional scholarships and awards. Employment status showed a high employment rate, with many graduates securing stable teaching positions locally. Graduates rated the relevance of their degree to their present work as highly relevant, highlighting competencies in research, communication, and leader-ship as pivotal in meeting workplace demands.The study concludes that the university's programs effectively prepare graduates for the teaching profession, though further im-provements are needed to address gaps in leadership opportunities and long-term career progression. Recommendations include enhanc-ing curriculum design to integrate emerging competencies, strength-ening pre-graduation training to reduce unemployment due to lack of experience, and developing targeted leadership programs to support career advancement. These initiatives aim better to align the univer-sity's offerings with labor market needs, ensuring sustained employ-ability and professional growth for graduates.